CUSTOMER VALUE PERFORMANCE, SATISFACTION AND RELATIONAL MARKETING ON PRIORITY CUSTOMER LOYALTY ( Case study of Bank ABC Surabaya Cendana Main Branch Office) - Enny Istanti; Achmad Daengs GS; Ruchan Sanusi; Sutopo; RM Bramastyo Kusumo Negoro; Ali Muhdor; Syafi’i (Universitas Kristen Indonesia Toraja, 2022)
Banking is a service industry that is very important in advancing the economy of a country. The purpose of this study is to determine whether there is an effect of variable customer value, satisfaction and relational marketing on customer loyalty Priority Bank XYZ Main Branch Office Surabaya Cendana. The data used in this study is primary data obtained by distributing questionnaires, using multiple linear regression analysis techniques. There is an influence between the independent variable and the dependent variable, as evidenced by a significant value of 6,328.10-26 <0.05. Partially, the customer value variable (X1) has a positive and significant effect on customer loyalty, the customer satisfaction variable (X2) has a positive and significant effect on customer loyalty and the relationship marketing variable (X3) has a positive and significant effect on customer loyalty. The most dominant variable is the relational marketing variable (X3) because the partial correlation value in the coefficients table is 62.29% greater than the partial correlation value of the other independent variables. customer value variables, customer satisfaction, and relationship marketing simultaneously have a significant effect on verified customer loyalty, customer value variables, customer satisfaction, and relationship marketing partially have a significant effect on proven customer loyalty and relationship marketing variables have a dominant influence on proven customer loyalty the truth. The most dominant variable is the relational marketing variable (X3) because the partial correlation value in the coefficients table is 62.29% greater than the partial correlation value of the other independent variables. customer value variables, customer satisfaction, and relationship marketing simultaneously have a significant effect on verified customer loyalty, customer value variables, customer satisfaction, and relationship marketing partially have a significant effect on proven customer loyalty and relationship marketing variables have a dominant influence on proven customer loyalty the truth. The most dominant variable is the relational marketing variable (X3) because the partial correlation value in the coefficients table is 62.29% greater than the partial correlation value of the other independent variables. customer value variables, customer satisfaction, and relationship marketing simultaneously have a significant effect on verified customer loyalty, customer value variables, customer satisfaction, and relationship marketing partially have a significant effect on proven customer loyalty and relationship marketing variables have a dominant influence on proven customer loyalty the truth.